2013
DOI: 10.1097/brs.0b013e3182a7eb7c
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Laminoplasty Compared With Laminectomy and Fusion in Patients With Cervical Myelopathy

Abstract: Weak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 10 publications
0
64
1
5
Order By: Relevance
“…In patients with multilevel CSM, neck pain is typically an indication to offer LPSF because previous studies have demonstrated a high incidence of new neck pain following laminoplasty, as high as 25% of patients. 7,27 However, according to the findings from this study among patients with matched postoperative cervical alignment and lordosis, follow-up pain incidence and severity were similar for patients who underwent laminoplasty or LPSF, despite the presence or absence of preoperative neck pain. This may suggest that postoperative cervical alignment and curve is a significant determinant in influencing the efficacy of either laminoplasty or LPSF in treating neck pain.…”
Section: 27mentioning
confidence: 85%
See 3 more Smart Citations
“…In patients with multilevel CSM, neck pain is typically an indication to offer LPSF because previous studies have demonstrated a high incidence of new neck pain following laminoplasty, as high as 25% of patients. 7,27 However, according to the findings from this study among patients with matched postoperative cervical alignment and lordosis, follow-up pain incidence and severity were similar for patients who underwent laminoplasty or LPSF, despite the presence or absence of preoperative neck pain. This may suggest that postoperative cervical alignment and curve is a significant determinant in influencing the efficacy of either laminoplasty or LPSF in treating neck pain.…”
Section: 27mentioning
confidence: 85%
“…4,24 Furthermore, pseudarthrosis becomes a concern with LPSF over time, and reported rates are as high as 38%. 27 However, the actual difference in perioperative morbidity and complications between multilevel laminoplasty and LPSF is relatively small and patients tolerate both procedures well. In fact, it has been suggested that when addressing more than 4 levels, postoperative pain following laminoplasty is greater than that in LPSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In multilevel anterior cervical fusion, the pseudarthrosis most commonly occurs at the lowest fusion level, and even with BMP-2 augmentation, the rate is approximately 10% [41]. After laminectomy and fusion, the pseudarthrosis rate was found to range from 1% to 38% in a recent systematic review [57]. Flexion and extension radiographs and CT scan can evaluate the fusion site (Fig.…”
Section: Pseudarthrosismentioning
confidence: 99%